Renal Transplant Artery Stenosis and Kinking: An Unusual Association - R. Haridan Sosa Barrios; Victor Burguera Vion; Ester Casillas Sagrado; Daniel Villa Hurtado; Sara Jiménez Álvaro; Irene Martín Capón; Milagros Fernández Lucas; Maite E. Rivera Gorrín (CINQUILL Medical Publishers Inc., 2023)
Renal artery stenosis of the kidney allograft associated with kinking is not a frequent finding. As a correctable cause of graft dysfunction, it is important to diagnose it as soon as possible to avoid further graft damage and improve graft and patient survival. As pulsed wave Doppler ultrasound mapping of the graft's renal arteries is essential to diagnose possible alterations, point of care ultrasound (POCUS) is a highly useful tool for early diagnosis. We present a case in which nephrologists performed this examination promptly allowing a timely diagnosis and treatment plan.